PENGARUH PENERAPAN SANKSI ADMINISTRASI TERHADAP TINGKAT KESADARAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KECAMATAN MELONGUANE KABUPATEN KEPULAUAN TALAUD - Ambanaga, Ardino s; LENGKONG, FLORENCE DAICY; Tulusan, Femmy M (Sam Ratulangi University, 2015)
ABSTRACTProperty tax is a tax leived for the person or entityy that actually has the rights to theland and property, or to benefit over the earth and the building, which aims to provide benefitsfor the survival. Implementation of the tax, it still has not reached level as expected. Generallybecause people still laqck confidence in the existence of the tax because they feel burdensome,and the payment often have difficulty, misunderstanding of what society and how taxes andthe difficualty of calculating and reporting.This study di kecamatan Melonguane island. Population and sample taken amounted to 33people. Data obtained from 10 employees district offices, 20 communities in the districtMelonguane, and three employees of the local revenue office with interview terstukture, theanalyzed with statistical information that simple linear regression analysis and the simplecorrelatio analysis of penelitian can be concluded that the effect of the application ofadministrastive sanctions running properly where this is caussed their public awareness andthe role of government in addressing the problem.